How do intrahousehold dynamics change when assets are transferred to women? Evidence from BRAC’s Challenging the Frontiers of Poverty Reduction—Targeting the Ultra Poor program in Bangladesh - Das, Narayan C.; Yasmin, Rabeya; Ara, Jinnat; Kamruzzaman, Md.; Davis, Peter; Behrman, Julia A.; Roy, Shalini; Quisumbing, Agnes R. (International Food Policy Research Institute, 2013)
Growing evidence shows that the distribution of individuals' ownership and control of assets within a household can have important implications for women’s empowerment and children’s well-being. Interventions that target assets to specific individuals can shift these intrahousehold dynamics, yet little evidence exists from rigorous evaluations. We study BRAC’s Challenging the Frontiers of Poverty Reduction—Targeting the Ultra Poor (CFPR-TUP) program in Bangladesh, which targets asset transfer (primarily livestock) and training to rural women in poor households. Previous research has shown large, significant positive program impacts at the household level. In this paper, we examine intrahousehold impacts using mixed methods. We focus on the Specially Targeted Ultra-Poor(STUP) component of the program, which targets households selected following a randomized controlled trial design. Adding a new round of data collection with quantitative sex-disaggregated information and qualitative exploration, we exploit the randomized design to assess intrahousehold impacts of STUP. Our analysis confirms that the program significantly increases household ownership of various assets but has complex effects on the targeted women. Quantitative estimates show increases in women’s sole and joint ownership of or control over transferred assets such as livestock, but a much greater increase in men’s sole ownership over nearly all other assets (including agricultural and nonagricultural productive assets, land, and consumer durables). These findings suggest that while the transferred assets tend to remain with women, new investments from mobilized resources are controlled by men. Moreover, the program reduces women’s mobility outside the home and their control over income, consistent with the transferred asset’s requiring maintenance at home. Qualitative findings are consistent with these quantitative results , but women’s contribution to their households is perceived as increasing their confidence and social capital, which they themselves value. Therefore, while provision of assets and training to women has ambiguous effects on women’s empowerment in terms of tangible assets and decisionmaking, women take intangibles into account and largely perceive positive (though still mixed) effects. The analysis shows that asset transfer targeted to women can increase women’s ownership of and control over the transferred asset itself but may not necessarily increase women’s intrahousehold bargaining position. Moreover, it reveals that outcomes valued by individuals may not always be tangible, highlighting the complexity of assessing whether interventions improve women’s empowerment.